2020
DOI: 10.4084/mjhid.2020.059
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of liver involvement in familial Mediterranean fever after introduction of canakinumab: a case report

Abstract: A 44-year-old Jewish woman with familial Mediterranean fever (FMF) developed non-alcoholic steato-hepatitis during colchicine treatment (2,5 mg per day), confirmed by both elastographic study and liver biopsy. A combined therapy with the interleukin-1 (IL-1) blocking agent canakinumab (150 mg every 4 weeks) and colchicine (at a reduced dose of 1.5 mg per day) was started. Three months later transaminases became normal, and six months later there was a marked improvement of liver fibrosis on the elastographic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The FDA has approved canakinumab for the treatment of Still's disease and it is sold under the brand name Ilaris. A study reported that treatment with canakinumab in combination with colchicine showed improvement in hepatic dysfunction due to familial Mediterranean fever [85]. Although it has shown promising effects in the management of cardiovascular disorders, its significant efficacy in the specific management of hepatic disorders has not been observed yet.…”
Section: Canakinumabmentioning
confidence: 99%
“…The FDA has approved canakinumab for the treatment of Still's disease and it is sold under the brand name Ilaris. A study reported that treatment with canakinumab in combination with colchicine showed improvement in hepatic dysfunction due to familial Mediterranean fever [85]. Although it has shown promising effects in the management of cardiovascular disorders, its significant efficacy in the specific management of hepatic disorders has not been observed yet.…”
Section: Canakinumabmentioning
confidence: 99%
“…Indeed, IL-1 antagonists are the treatment of choice in refractory or colchicine-intolerant cases of FMF, and a large experience with anakinra and canakinumab is now available for thousands of colchicine-resistant patients [40]. Canakinumab seems to have a positive effect on different severe inflammatory symptoms by controlling disease activity and overall inflammation [41]. A better interpretation of FMF mutations in various clinical sceneries has led to coin the umbrella-term "pyrin-associated autoinflammatory diseases", including all non-FMF diseases caused by MEFV-related pyrin defects, such as periodic undefined fevers, periodic fever/aphthosis/ pharyngitis/adenitis syndrome-like pictures and neutrophilic dermatosis [42].…”
mentioning
confidence: 99%